Do or Die : Reluctant Heroes - Brockmann, Suzanne (New York : Ballantine Books, 2014)
"Former Navy SEAL Ian Dunn has been tasked by a mysterious government agency with rescuing two kidnapped children believed to have been taken prisoner in a South American embassy. Leading the mission alongside Phoebe Kruger, the new hire at the prestigious law firm where Dunn is a longtime client, Dunn will embark on a race against time while simultaneously dealing with an equally pressing danger -- he's being hunted by the mob for a job gone bust. In the midst of all this, Phoebe gets sucked deeper and deeper into Dunn's clandestine world, and Dunn faces some surprises of his own as he slowly becomes aware of Phoebe's sharp intelligence, keen sense of humor and generous heart--things he's been missing all his life"--
Keywords: Private investigators -- Fiction; Kidnapping -- Fiction; Embassy buildings -- Fiction -- South America; FICTION / Romance / Contemporary; FICTION / Romance / Suspense; FICTION / Romance / General; Romantic suspense fiction